Estudio del impacto del financiamiento de las empresas de la ciudad de Quito en el periodo 2005-2010 a través de la bolsa de valores. - Montenegro Marín, Iván David (2014)
This study contains information about what the Stock market exchange is, and its development in Ecuador, also it is about the traditional sytem of financing. It means, what is the impact of the Quito enterprices financing trought the market stock exchange. It is also about the traditional way of finance, stock extrange, and the main requierements for the new participants of this market. It includes the enterprices that was in the Quito stock exchange in the year of the study, 2005-2010. The study also includes information about the growing of stocks in the Quito stock exchange, and what is the main purpose of the enterprices when they sell their stocks. The study discovered that the enterprices had a similar purpose that was payment of their bills and buying new machines and new enterprices.